Gambogic acid targets HSP90 to alleviate DSS-induced colitis via inhibiting the necroptosis of intestinal epithelial cells - Wang, Yuanyuan; Liu, Siqi; Lu, Keyi; Xu, Erping; Wang, Zhibin (Frontiers in Pharmacology, 2025)
Abnormal elevations in the mortality of intestinal epithelial cells (IECs) are indicative of intestinal inflammation. Necroptosis of IECs represents a pro-inflammatory form of cell death, and modulation of IECs necroptosis may mitigate subsequent intestinal inflammation and preserve the integrity of the intestinal barrier. Currently, safe and effective preventive measures are lacking. In the Traditional Chinese Medicine theory, necroptosis of IECs leads to the destruction of the intestinal barrier in a manner associated with “heat and toxicity”, exacerbating intestinal inflammation. Heat shock protein 90 (HSP90) has been identified as a regulator of key proteins involved in necroptosis signal pathway including RIPK1/3 and MLKL. Gambogic acid (GA), the primary active compound found in Garcinia hanburii Hook. f., a traditional Chinese medicine used for detoxification and hemostasis, has not been studied for its potential therapeutic effects in ulcerative colitis previously. This study investigated the protective effects of GA on dextran sodium sulfate (DSS)-induced colitis in mice, as well as the underlying molecular mechanisms. GA was observed to significantly ameliorate DSS-induced enteritis and enhance intestinal barrier function. Concurrently, it reduced the phosphorylated expression levels of RIPK1/3 and MLKL. The underlying mechanism may be related to the suppression of HSP90 expression.